Dynamic Models and Reciprocity - Bun, M.; Chan, Felix; Harris, Mark (Springer, 2017)
This book is aimed at filling this widening gap. The first theoretical part of the volume is providing the econometric foundations to deal with these new high-dimensional panel data sets.